2021
DOI: 10.3389/fimmu.2021.700782
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Based Prediction of COVID-19 Severity and Chronicity Decoded Using Machine Learning

Abstract: Expression of CCR5 and its cognate ligands have been implicated in COVID-19 pathogenesis, consequently therapeutics directed against CCR5 are being investigated. Here, we explored the role of CCR5 and its ligands across the immunologic spectrum of COVID-19. We used a bioinformatics approach to predict and model the immunologic phases of COVID so that effective treatment strategies can be devised and monitored. We investigated 224 individuals including healthy controls and patients spanning the COVID-19 disease… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
179
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(190 citation statements)
references
References 51 publications
10
179
0
1
Order By: Relevance
“…Conditions that “preload” the sympathetic nervous system toward inflammation, (e.g., hypertension, obesity, diabetes) predispose catastrophic failure of this feedback loop, resulting in damaging cytokine levels seen in severe COVID-19 ( Porzionato et al, 2020 ). The dysregulated neuroinflammatory state observed in Long COVID ( Patterson et al, 2021 ) represents a subtler form of dysautonomia that appears to be responsive to SGB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions that “preload” the sympathetic nervous system toward inflammation, (e.g., hypertension, obesity, diabetes) predispose catastrophic failure of this feedback loop, resulting in damaging cytokine levels seen in severe COVID-19 ( Porzionato et al, 2020 ). The dysregulated neuroinflammatory state observed in Long COVID ( Patterson et al, 2021 ) represents a subtler form of dysautonomia that appears to be responsive to SGB.…”
Section: Discussionmentioning
confidence: 99%
“…Time to resolution of symptoms may be prolonged in cases with organ damage, but generally correlates with severity of disease course. However, approximately 30% of symptomatic and 5% of asymptomatic individuals who recover from acute infection develop a distinct proinflammatory cytokine/chemokine profile ( Patterson et al, 2021 ) and experience a range of symptoms that persist indefinitely ( Logue et al, 2021 ). The constellation of symptoms, which can range from mild to debilitating, is known colloquially as “Long COVID” and formally as Post-Acute Sequelae of SARS-CoV-2 infection (PASC).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who succumb to severe COVID-19 often present an imbalanced immune response with exacerbated inflammation and dysregulated T cell activation and other counteracting activities [ 86 ]. Thus, the use of anti-cytokine and immunomodulatory medication was postulated to diminish inflammatory-mediated organ damage in the general population and SOT recipients.…”
Section: Therapeutic Options In Sot Recipients In Covid-19mentioning
confidence: 99%
“…However, female sex, high numbers of symptoms and antibodies to SARS-CoV-2 may play a role in pathogenesis, although some studies have found no significant differences. New lines of research investigate specific biomarkers to establish clusters for both severe COVID-19 and PACS using machine learning techniques to resolve the discrepancies addressed above ( 23 ). We must ensure the follow up of these patients, with a view to finding out how long these symptoms persist and whether they develop into chronic disorders.…”
mentioning
confidence: 99%